RANCANGAN POSTER BIOLOGI PADA MATERI BAKTERI KELAS X SMA - Syafitri, Desrianty; Sayuti, Irda; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of the poster design in highschool Biologi learning class X material on bacteria. This research was conductedat theBinawidya Riau University in Desember2020–Januari 2021. This research wasconducted in 2 stages: the experimental stage and the second stage is Poster Designthat is analysis of the potential development of learning media for high school biologiclass X Bcteria material. The study used an experimental method of descriptivequalitative research design. Based on the potential analysis it was found thatoptimization of nutrient ratio for he growth of Bacillus cereus Strain IMB-11bacteriacan be used as a learning media poster design for class X high schoolbacteria material 3.5KD.Key Words: Poster, Bacteria, Hidrocarbonoclastic.